ANALISIS SEMIOTIKA DAN NILAI KEBUDAYAAN MINANGKABAU DALAM FILM TENGGELAMNYA KAPAL VAN DER WICJK - Hidayat , Muhamad Mamduh (Fakultas Ilmu Dakwah dan Komunikasi, 2022)
Film is a form of mass communication that depends on the information it conveys and has the power to influence and shape the attitudes of its viewers. This research, which falls into the category of descriptive qualitative research, explores how Minangkabau cultural values are represented in the film